HUBUNGAN ANTARA SIKAP TERHADAP EVALUASI GURU BK DENGAN KETERLAKSANAAN PROGAM BIMBINGAN DAN KONSELING - Dina Rahmawati Hapsyah; Nina Fitriyani; Riska Handayani; Theodora Nurmalia; Afan Abdul Jabbar; Deni Purwanto; Aip Badrujaman (Jurnal Renaissance, 2019)
Attitudes towards program evaluation need to be owned by guidance and counseling teachers in implementing programs so that the services provided are of higher quality. This study aims to look at the relationship between the teacher's counseling and counseling attitudes towards program evaluation and the implementation of guidance and counseling programs. In this study, the subjects of the study population were guidance and counseling teachers at Serang District (Banten) State Middle School, amounting to 30 people. The instrument used is the teacher's attitudes of guidance and counseling towards the evaluation of basic services used to obtain information about the teacher's attitudes of guidance and counseling on evaluating basic services and instruments for the implementation of guidance and counseling programs used to describe the evaluations carried out by teachers guidance and counseling . The results showed that 50% of the guidance and counseling teachers had good knowledge of the guidance and counseling teacher evaluation, as many as 63 guidance and counseling teachers had good opinions on the evaluation of guidance and counseling. The results of the study on the implementation of the guidance and counseling program evaluation showed that 47% of guidance and counseling teachers carried out an evaluation of counseling and guidance program planning, 53% of guidance and counseling teachers carried out process evaluation, 59% of guidance and counseling teachers carried out evaluation results, while evaluation of counseling programs was 53 %. Keywords: Attitudes toward Guidance and Counseling Teacher Evaluation, Implementation of Guidance and Counseling Programs